Protracted alcohol withdrawal syndrome due to chronic alcohol consumption: a case report - Erdoğan, Serap; Eren, Nurdan; Arıkan, Zehra (Journal of Dependence, 2006)
A lot of neurological and psychological complications can occur due to chronic alcohol consumption. Especially during the alcohol cessation periods, clinical situations in which the various disturbances due to alcohol consumptions and alcohol withdrawal symptoms are together, diagnosis may be so difficult. Typically alcohol withdrawal syndrome starts within 6-24 hours after the cessation of overly alcohol consumption. Most of the symptoms which occur during withdrawal period seem to be related with the adaptive changes of the neurotransmitter, neuropeptid and neuroendocrin systems due to continuous alcohol consumption. In some patients it has reported that memory disturbances, sudden subjective distrress complaining, calmness periods and even transient psychotic epizodes occuring after the end of the acut withdrawal syndrome may be relate with the protracted withdrawal syndrome. In the reported case, the protracted alcohol withdrawal syndrome, alcohol delirium, and cerebellar degeneration due to alcohol consumption are discussed in a patient who has used alcohol for 23 years. Especially in the treatment of a patient with long term alcohol consumption, it is important to think about these possible complications and to treat withdrawal symptoms sufficiently and properly.